Practice based research in visual arts education: An approaches to research work book / Raiha Shahanaz Redzuan ... [et al.] - Redzuan, Raiha Shahanaz; Othman, Noor Farhani; Shah Silah, Sumardian; Isa, Badrul; Ahamed Kamal, Akmal (2022)
Universiti Teknologi MARA (UiTM) Faculty of Education's experience, implementation and understanding of visual arts is based on teaching and learning activities in visual arts education subject within the B.Ed (Hons.) Art and Design Education course. Various programs and activities are conducted through the subject for trainee teachers to learn and to experience the importance of understanding a variety of visual arts as it benefits their future teaching. It is admitted that the ability to understand various visual arts education is not an easy task and may most of the time, test the patience and emotions of teachers. Therefore, training is conducted by the faculty in hoping that the future teachers may become the mediator to impart knowledge entailing visual arts education in Malaysia. Hence, future graduates are also expected not to have only abilities in using good pedagogical techniques in teaching but also to attract students to be actively involved in the process of learning in class.